Oxidation-resistant and highly sensitive cellulose paper pressure sensor for wearable electronics - Deristisya Zahra; Mohammad Zarei; Jinwoo Hwang; Eunho Lee; Seung Goo Lee (Carbohydrate Polymer Technologies and Applications)
Nonbiodegradable polymers widely used in wearable electronics and sensors contribute significantly to e-waste and environmental toxicity. While the integration of biodegradable biopolymers offers a promising solution, their application is hindered by challenges in achieving reliable conductivity, sensitivity, and stability. In this study, we develop a biodegradable cellulose paper pressure sensor coated with silver nanowires (AgNWs), Ti3C2Tx (MXene), and reduced graphene oxide (rGO). The AgNWs/MXene/rGO-coated cellulose paper capacitive pressure sensor demonstrates high sensitivity (1.031 kPa−1) over a wide pressure range (0–40 kPa), remarkable robustness (5000 cycles), and excellent sensing stability (>44 days). Moreover, the incorporation of rGO nanosheets enhances the resistance and stability of the AgNWs/MXene-coated paper-based composite against oxidation. Furthermore, various sensory architectures, including origami butterfly and kirigami snowflake pressure sensors, have been demonstrated using AgNWs/MXene/rGO-coated cellulose paper for a wide range of physiological sensing applications. These diverse applications highlight the versatility, adaptability, and applicability of the AgNWs/MXene/rGO-coated paper-based capacitive pressure sensor for fabricating biodegradable wearable sensors.